The Tet Offensive : Intelligence Failure in War - Wirtz, James J., 1958- (Book collections on Project MUSE., 1991)
"In this account of one of the worst intelligence failures in American history, James J. Wirtz explains why U.S. forces were surprised by the North Vietnamese Tet Offensive in 1968. Wirtz reconstructs the turning point of the Vietnam War in unprecedented detail. Drawing on Vietcong and recently declassified U.S. sources, he is able to trace the strategy and unfolding of the Tet campaign as well as the U.S. response."--Back cover